O patrimônio documental e a memória da universidade: um instrumento de acesso aos atos legais e normativos da UFSM - Carpes, Franciele Simon (2013)
His paper presents a study on archival description and dissemination of the resolutions of the Rector at Universidade Federal de Santa Maria. Due to its probative value and informative documents resulting from legal acts and regulations of the Universidade Federal de Santa Maria are considered permanent, i.e., they are historical documents that make up the documentary heritage of the University. Currently, most of these documents are accessible only on paper. Still, the number of queries is high due to the relevance of these documents and their use for decision making. The availability of these documents, using technological tools, would be, therefore, a greater and better access to them. In this context, the aim of this study is the description of archival documentary heritage of the Office of the Rector, at Universidade Federal de Santa Maria, in order to spread their legal and normative acts. The research method chosen is the case study, and, as instruments of data collection observation and document analysis were used. To accomplish the description framework of standards and standards for the development of metadata description and drawing instrument description have been established. This standards and metadata framework was implemented in the electronic system of the University (SIE). The collection has been digitized and described according to Brazilian Standard Archival Description - NOBRADE. Subsequently, the instrument was published online: a catalogue of the Resolutions of the Rector. The catalogue facilitated the search and access to the resolutions of the rector, that were already widely consulted documents. Being online, the instrument allowed greater access to this body and assists in preserving the original paper for it avoids handling. The development of this research, describing and preserving documentary heritage is significant both for the University and for the Archives Administration. Thus, the research contributed to the studies regarding the archival description, the use of its standards, and the use of information technology to provide the results of this description.